COMPUTER TECHNOLOGY APPLICATIONS WITH VISUAL BASIC 6.0 APPLICATION FOR SEEKING KPK (MULTIPLES OF THE GUILD'S SMALLEST) AND FTB (GREATEST COMMON DIVISOR) FOR ELEMENTARY SCHOOL STUDENTS - Suparno Suparno (Jurnal Sistem Informasi, 2006)
In searching for the KPK (Earned Guild Smallest) and FTB (Guild Biggest Factor) inmath by using computer technology is rarely used for those in elementary schoolchildren. Therefore, with the Microsoft Visual Basic 6.0 applications to make it easierto find the commission and the FTB plus a bit of visual elements in it that can beinteresting for those in elementary school children.